2014
DOI: 10.1111/cas.12350
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose‐escalation study of buparlisib (BKM120), an oral pan‐class I PI3K inhibitor, in Japanese patients with advanced solid tumors

Abstract: Buparlisib (BKM120) is an oral pan-phosphatidylinositol 3-kinase inhibitor, targeting all four isoforms of class I PI3K (α, β, γ and δ). This open-label Phase I dose-escalation study was conducted to determine the maximum tolerated dose of continuous daily buparlisib in Japanese patients with advanced solid tumors. Secondary objectives included safety and tolerability, pharmacokinetics, antitumor activity and pharmacodynamic marker changes. Fifteen patients were treated at 25 mg/day (n = 3), 50 mg/day (n = 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 48 publications
11
63
0
1
Order By: Relevance
“…In early phase clinical trials, buparlisib demonstrated promising efficacy and manageable safety profile providing the rationale for further clinical evaluation of buparlisib [2124]. The Neo adjuvant P I3K inhibition in H ER2 O ver E xpressing B reast canc E r (NeoPHOEBE) trial was designed to evaluate the efficacy and safety of buparlisib plus trastuzumab and paclitaxel as neoadjuvant treatment for patients with untreated HER2+ primary breast cancer and the potential predictive value of PIK3CA mutations for higher tumour responses.…”
Section: Introductionmentioning
confidence: 99%
“…In early phase clinical trials, buparlisib demonstrated promising efficacy and manageable safety profile providing the rationale for further clinical evaluation of buparlisib [2124]. The Neo adjuvant P I3K inhibition in H ER2 O ver E xpressing B reast canc E r (NeoPHOEBE) trial was designed to evaluate the efficacy and safety of buparlisib plus trastuzumab and paclitaxel as neoadjuvant treatment for patients with untreated HER2+ primary breast cancer and the potential predictive value of PIK3CA mutations for higher tumour responses.…”
Section: Introductionmentioning
confidence: 99%
“…The phase II randomized study (Neophobia, NCT01816594) testing neoadjuvant Trastuzumab and paclitaxel +/− buparlisib in early-stage breast cancer patients, was stopped prematurely owing to a lack of pCR benefit and higher toxicity in the Buparlisib arm. [13,44] Notably no additional benefit was seen in the PIK3CA mutant subgroup receiving the pan- PI3K inhibitor. In stage IV squamous non-small cell lung cancer patients, both phase Ib/II trials testing the addition of Buparlisib in the first-line setting to 3-weekly carboplatin and paclitaxel (BASALT2; NCT01820325) and in the second-line setting to 3-weekly docetaxel (BASALT-3; NCT01911325), were terminated due to the challenging safety profile and marginal anti-tumor activity observed.…”
Section: Discussionmentioning
confidence: 99%
“…[9–13] Preclinical data have shown that as a class, PI3K inhibitors can enhance the antitumor activity of cytotoxic chemotherapy and combinatorial strategies with buparlisib are being explored with preliminary signs of clinical activity. [14–17] We previously reported a single-center dose escalation study ( n=30) of daily buparlisib combined with two parallel schedules of carboplatin (AUC 5) and paclitaxel (175 mg/m2 on day 1 with pegfilgrastim support or 80 mg/m2 on day 1, 8, and 15 without pegfilgrastim support) of an every 3 (q3) or q4 week cycle, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Combinational use of BKM120 with cisplatin exhibits enhanced efficacy 57 . A phase I clinical study in Japan showed that BKM120 had a manageable safety profile, and could be rapidly absorbed in a dose-proportional manner 58 . Clinical efficacy and tolerability of BKM120 were also evaluated in postmenopausal women with estrogen receptor–positive metastatic breast cancer, in combination with fulvestrant using daily or intermittent schedules (days 1–5 each week).…”
Section: Pi3k Inhibitors Approved or In Clinical Trialsmentioning
confidence: 99%